2018
DOI: 10.1186/s12864-018-5087-x
|View full text |Cite
|
Sign up to set email alerts
|

Parental experience modifies the Mimulus methylome

Abstract: BackgroundTransgenerational plasticity occurs when the environmental experience of an organism modifies the growth and development of its progeny. Leaf damage in Mimulus guttatus exhibits transgenerational plasticity mediated through differential expression of hundreds of genes. The epigenetic mechanisms that facilitate this response have yet to be described.ResultsWe performed whole genome bisulfite sequencing in the progeny of genetically identical damaged and control plants and developed a pipeline to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 82 publications
(106 reference statements)
1
26
0
Order By: Relevance
“…Genomic analysis may provide clarity as to whether these traits, and the genes responsible for them, are under selection in nature, or are evolving by drift. Likely candidates include genes regulating DNA methylation (e.g., Colicchio et al 2018;Rendina González et al 2018;Van Dooren et al 2020), or small RNAs (Zhong et al 2013), both of which have been implicated in the regulation of transgenerational plasticity.…”
Section: Future Directionsmentioning
confidence: 99%
“…Genomic analysis may provide clarity as to whether these traits, and the genes responsible for them, are under selection in nature, or are evolving by drift. Likely candidates include genes regulating DNA methylation (e.g., Colicchio et al 2018;Rendina González et al 2018;Van Dooren et al 2020), or small RNAs (Zhong et al 2013), both of which have been implicated in the regulation of transgenerational plasticity.…”
Section: Future Directionsmentioning
confidence: 99%
“…Previous experimental work in this same M. guttatus RIL94 genotype identified 3731 differentially methylated genomic regions (DMRs) [ 13 ] and 919 differentially expressed genes (DEGs) [ 14 ] in the progeny of leaf wounded plants. To test component (2) of our working model, whether proximity of sRNA loci increases the probability that protein coding regions will be differentially methylated or differentially expressed in progeny of leaf wounded plants, we tested whether genomic regions that overlapped with sRNA loci were more likely to have previously been identified as transgenerationally labile.…”
Section: Resultsmentioning
confidence: 99%
“…In M. guttatus , altered trichome production in the progeny of wounded plants [ 54 ] has inspired a number of follow-up experiments designed to elucidate the underlying molecular mechanisms for the transmission of non-genetic information between generations. Past work has demonstrated the genotype specificity of this response [ 54 , 55 ], pointed at substantial differential gene expression associated with parental wounding [ 14 , 56 ] and suggested that the majority of differential methylation associated with parental wounding is associated with transposon CHH methylation but that genic CG methylation is also impacted [ 13 ]. Additionally, recent work has demonstrated transgenerational trichome plasticity transmitted through both the maternal and paternal germline, with maternal but not paternal transmission likely involving DNA methylation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations